THE ROLE OF MASS MEDIA IN THE DEVELOPMENT OF CIVIL SOCIETY IN NEW UZBEKISTAN - Dadasheva, Akida Abdujabbarovna (Educational Research in Universal Sciences, 2023)
The purpose of the study was to analyze the place of media in the development of civil society in Uzbekistan. Media in civil society (media) as a democratic institution as the main guarantees of self-government of society is the content analysis of the legislation of Uzbekistan. In civil society, the focus is on a general and specific analysis of international and national media documents. As a result, tasks were developed to further strengthen the role and role of the media in the system of institutions of civil society, to ensure the constitutional rights of citizens to freedom of speech and freedom of choice.